Al-Shajarah: Journal of the International Institute of Islamic Thought and Civilization (ISTAC), Special Issue: Islamic banking and finance - Haron, Razali (IIUM Press, International Islamic University Malaysia, 2019)
Al-Shajarah Special Issue: Islamic Banking and Finance For this Al-Shajarah Special Issue, the Islamic Banking and Finance takes the front by focussing on Islamic Social Finance issues. Islamic Social Finance issues are rapidly gaining the attentions of all players in the field and Al-Shajarah plays its part in presenting several selected related issues, highlighting the challenges and recommending possible remedies and solutions based on either empirical evidences or analyses of current scenarios and best practices. Among the issues discussed are zakat contributions, the impact of financial crimes on performance of firms, Islamic Social Finance and the imperative for social impact measurement, the value-based intermediation approach on Islamic Social Finance, the potential in reviving waqf through crowd-funding technology, crypto-currency, zakat distribution on social welfare, Islamic Fintech investment innovation, the role of Islamic Social Finance and the insurance practices which can be resolved by introducing takaful in India. This special issue starts with an extensive examination on the impact of corporate social responsibilities particularly on the application of Islamic Social Finance which is zakat contribution by Islamic banks on their financial performances. The findings show that zakat contribution has positive significant impact on Islamic banks’ financial performance. The next paper highlights the impact of financial crimes on the reputation of Islamic financial institutions. The study then proposes a conceptual framework which may safeguard public trust and confidence towards the integrity of Islamic financial institutions from reputation risks due to financial crimes. Another study highlights the importance of social impact measurements in Islamic finance by exploring and critically reviewing existing related literature. The ongoing criticisms of Islamic finance failing to fulfil its purposes and objectives indicate gaps between its theory and practice. This study thus proposes mechanisms or frameworks for Islamic financial institutions to measure the social impact of their operations, products and services to realise the full potential of Islamic finance. This can be done through a stakeholder-based approach and assimilating frameworks of Value-Based Intermediation (VBI), Maqasid al-Shari’ah, and Sustainable Development Goals. With the introduction of Sustainable Development Goals or SDGs in 2015, the notion of sustainability and impactful services provide an inspiration to the dual financial services industries in Malaysia. While Shari’ah provides holistic objectives in comparison to SDGs, the approach of VBI opens a new pragmatic dimension for IFSI in providing impactful and beneficial services to the public at large. This study provides evidence that VBI facilitates Islamic banks to provide impactful services to their customers and other innovative strategies based on Islamic Social Finance. Another study on waqf is discussed here but focusing on the case in Thailand. This study looks at the opportunity of reviving waqf in Thailand through crowd funding platforms. Such revival of waqf is essential for the society at large, especially for the Muslim community. The revival of waqf may provide essential assistance in alleviating poverty and gives an equal opportunity for economic participation particularly in Thailand. The crypto-currency is a fairly new phenomenon in Malaysia thus the next study intends to examine the characteristics of Bitcoin currency based on the requirements of High-Quality Liquid Assets (HQLA) standards of Basel III and compare its volatility structure with other traditional asset classes that are already recommended by Basel III as HQLA. The findings provide appropriate information about Bitcoin asset behaviour compared to other traditional asset classes which will enable them to make the right investment decision with regard to hedging, diversification and liquidity risk management. The findings of this study may assist in evaluating the suitability of including crypto assets into HQLA to improve the liquidity requirement standards and ensure that banks have an adequate amount of HQLA specifically during times of financial turmoil. Another study examines the effectiveness of yearly zakat distribution as an instrument for social welfare in the state of Selangor - Malaysia. Overall, the study found that the zakat distribution contributes significantly to social welfare through education but contributes inadequately through income. This indicates that the current zakat distribution system in Selangor provides only a marginal influence on increasing the income of the poor and insignificant to social welfare through healthcare, implying insufficient distribution channels. A social health insurance policy for zakat beneficiaries can be the remedy to this flaw. This can be done via ratification of insurance plan between zakat agencies and insurance companies to cover the basic health needs for zakat recipients. Another issue highlighted in this special issue is peer-to-peer financial services which are increasingly becoming significant game changers in the financial sector across the globe. Peer-to-peer arrangement connects crowd-funding investors with entrepreneurs through more transparency, speed dealings and almost free from complications in the documentation. This paper attempts to develop a new peer-to-peer financing which is based on the Musharakah Smart Contract Model, in which the investors would be crediting their investments for Musharakah purposes with virtual lenders for specific Shari‘ah compliant businesses and share in the profit, based on an agreed dividend under the Musharakah principles. It also highlights the potential structures, cyber risks, and devices to mitigate them by using Musharakah standards and measures within the Shari‘ah principles. The role of Islamic Social Finance is explored further and this time in achieving the Sustainable Development Goals, particularly goal number two, “end hunger, achieve food security and improved nutrition and promote sustainable agriculture”. Three Islamic Social Finance tools namely infaq, waqf and zakat are discussed together with Ihya al-Mawat and al-Iqta’. Infaq, waqf and zakat are found to be an excellent alternative philanthropies’ fund. Expanding quality agricultural land through Ihya al-Mawat and al-Iqta’ can be the best alternatives to achieve the long-term target i.e. sustainable agriculture. Working together regionally or internationally in achieving the goal, especially for developing and least developed countries is ultimately recommended. Shifting to focusing the issue of takaful in India, this particular study focuses on how unethical issues in insurance can be resolved by introducing takaful in the country. Based on the interviews conducted, the undesirable issues can be resolved if takaful is offered and the operators abide by the Shari’ah requirements. Takaful is not solely for the Muslims. Besides offering the guarantees and securities that conventional insurance does, takaful contains an added feature particularly the fact that takaful is free from uncertainty, usury and gambling. Thus, the perfect tool to resolve the unethical issues existed in the insurance industry in India.